2012
DOI: 10.1007/s11999-011-2161-y
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Failure of Ceramic-on-Ceramic and Metal-on-Metal Hip Arthroplasties

Abstract: Background Few large series of hard bearing surfaces have reported on reasons for early failure. A number of unique mechanisms of failure, including fracture, squeaking, and adverse tissue reactions, have been reported with these hard bearing surfaces. However, the incidence varies among the published studies. Questions/purposes To confirm the incidences, we identified the etiologies of early failures of hard-on-hard bearing surfaces for ceramic-on-ceramic and metal-onmetal THAs. Methods We retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
1
34
1
1
Order By: Relevance
“…The fixation of CoC cementless cups has been improved using modern porous coatings [4,13,14,30] but remains a weak point of this bearing, particularly when considering the low rate of osteolysis that, contrary to MoP, did not contribute to cup loosening. Our results differ from the study by Porat et al [27] that identified femoral loosening as the main reason for revision of CoC THA (13 of 38 [34%]). After revisions for infection (n = 39), revisions directly related to ceramic use (including impingement, squeaking, ceramic breakage, and incorrect ceramic insertion) were the third most common reason for revision in our study (n = 37) ( Table 2).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The fixation of CoC cementless cups has been improved using modern porous coatings [4,13,14,30] but remains a weak point of this bearing, particularly when considering the low rate of osteolysis that, contrary to MoP, did not contribute to cup loosening. Our results differ from the study by Porat et al [27] that identified femoral loosening as the main reason for revision of CoC THA (13 of 38 [34%]). After revisions for infection (n = 39), revisions directly related to ceramic use (including impingement, squeaking, ceramic breakage, and incorrect ceramic insertion) were the third most common reason for revision in our study (n = 37) ( Table 2).…”
Section: Discussioncontrasting
confidence: 99%
“…This is an important finding because the time to revision of CoC THA was not mentioned in previous studies [27] or easy to extract from registries (the Australian register mentioned 2109 of 65,114 CoC THA revisions [3.2%] but not the revision rate before 5 years) [32]. Our results are in accordance with the Danish register indicating that 63 of 71 (88%) CoC THAs were revised before 5 years of followup [35].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…that require revision surgery and that are not prevented by simple choice of bearing surface (Table 3). Even aseptic loosening cannot be completely resolved using one specific bearing surface because of its multifactorial etiology 32 . On the other hand, the rate of osteolysis was diminished as a direct consequence of using ceramic bearings.…”
Section: Clinical Evidence For Ceramic-on-ceramic Thamentioning
confidence: 99%